“Maybe Tightening the Collar is the Way to Do It”: Naturalizing Oppression in Teacher Discourse on Student Learning - Kitts, Hope (Critical Education, 2024)
As part of a larger study, through this research I examined the ideological foundations of public school teachers’ interpretations of Paulo Freire’s Pedagogy of the Oppressed. I discovered that White teachers in this study talked about oppression in ways that implied it was a natural part of life, and even in some cases necessary for learning. Here I ask: What does teachers’ acceptance and naturalization of oppression mean for student learning and educational outcomes more broadly? Using a Critical Discourse Studies (CDS) framework I use ideological critique to present and critically examine metaphors of violence and control as voiced by two participants in the study, Janet and Pam. Further, I show how the one participant of color in the study challenged his colleagues’ assumptions about human nature and individuality, which Janet and Pam used to rationalize oppression. These findings have implications for teacher education and teacher professional development insofar as I urge teacher educators to examine how teachers think and talk about oppression and their role in sustaining or challenging the status quo through their teaching.